2007
DOI: 10.1111/j.1600-051x.2007.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease increases the risk of severe pre‐eclampsia among pregnant women

Abstract: These results indicate that the presence and severity of periodontal disease seems to increase the risk for not only the occurrence but also the severity of pre-eclampsia in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
5
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 44 publications
(53 reference statements)
8
70
5
5
Order By: Relevance
“…There are several studies that reported similar result (9,18,19). These studies support the inflammatory model of preeclampsia with an indirect infectious trigger leading to acute atherosclerosis in preeclampsia and subsequent chronic atherosclerosis and development of cardiovascular disease (20).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There are several studies that reported similar result (9,18,19). These studies support the inflammatory model of preeclampsia with an indirect infectious trigger leading to acute atherosclerosis in preeclampsia and subsequent chronic atherosclerosis and development of cardiovascular disease (20).…”
Section: Discussionsupporting
confidence: 65%
“…In this study periodontal disease as a combination of gingivitis and periodontitis was more frequently observed among the cases with mild preeclampsia compared to the severe form. However, a positive association was found between severity of preeclampsia and the intensity of periodontal disease in a recent study (18). Ruma et al reported that the risk of preeclampsia was increased with the severity of periodontal disease and C-reactive protein ≥ 75 th percentile being an indicator of maternal systemic inflammation (22).…”
Section: Discussionmentioning
confidence: 95%
“…6,[16][17][18][19][20][21][22][23] Eight of the ten studies have documented positive associations between maternal periodontal disease and preeclampsia risk. 6,[15][16][17][18][19][20][21] For instance, Boggess et al, in their cohort study of 763 women in North Carolina, reported that women with severe periodontitis at delivery, defined as ≥15 tooth sites with PD ≥4 mm, had a 2.4-fold increased risk of preeclampsia as compared with periodontally healthy women (OR = 2.4; 95% CI: 1.1-5.3).…”
Section: Maternal Periodontal Diseasementioning
confidence: 99%
“…In addition, a recent study of mothers of PLBW infants, with otherwise low risk, had significantly more periodontal disease than a similar group of women with normal weight infants at birth. The association observed between generalized periodontitis and induced preterm birth shows the strength, along with the extent of periodontitis [31][32][33] . There is conflicting research results regarding the relationship between periodontal diseases and adverse pregnancy events.…”
Section: Pregnancy and Periodontal Diseasementioning
confidence: 94%
“…Znatno više u odnosu na sličnu grupu porodilja s normalnom telesnom masom beba na rođenju. Ispitivana veza između generalizovane parodontopatije i prevremenog rođenja pokazuje jačinu uporedo sa stepenom težine parodontopatije [31][32][33] . Postoje kontradiktorni rezultati istraživanja odnosa između parodontopatije i neželjenih ishoda trudnoće .…”
Section: Pregnancy and Periodontal Diseaseunclassified